Crowd: uma rede social estruturada em comunidades - Antoniazi, Douglas (Universidade do Vale do Rio dos Sinos, 2013)
Social networks provide a new form of communication that still preserves our social interactions. Due to the popularization of mobile devices, such as smartphones and tablets, people now use these resources as their main form of interaction. Additionally, people seek groups that have similar areas of interest to gain and share information. The purpose of this paper is to present the test model App named Crowd. Crowd is a social network App that is structured to allow users to find other people within the community with similar interests in order to exchange information with one another. The test model Crowd App was tested and evaluated using Android technologies. It was proved to not only be user friendly but also that it can improve the daily lives of people.
Keywords: Redes sociais; Estrutura em comunidades; Computação móvel; Social networks; Community structure; Mobile computing